2017
DOI: 10.1016/j.jvs.2017.02.036
|View full text |Cite
|
Sign up to set email alerts
|

Trends and outcomes in endovascular and open surgical treatment of visceral aneurysms

Abstract: Endovascular VAA repairs are increasing. Despite patients' having worse comorbidities and more nonelective admissions, endovascular therapy appears to be associated with decreased mortality and complications and shorter hospital stays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…After reviewing the titles and abstracts, 3873 studies were excluded, with 616 studies retained for further detailed evaluation. Based on the inclusion and exclusion criteria, 595 studies were excluded, leaving 21 ( n = 21) cohort studies 1115,1732 reporting clinical data of interest and meeting the inclusion criteria (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…After reviewing the titles and abstracts, 3873 studies were excluded, with 616 studies retained for further detailed evaluation. Based on the inclusion and exclusion criteria, 595 studies were excluded, leaving 21 ( n = 21) cohort studies 1115,1732 reporting clinical data of interest and meeting the inclusion criteria (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Advantages of endovascular techniques are their minimally invasive nature, shorter recovery time, and lower risk of morbidity and death 8 . However, TAE may not always be technically feasible because of difficulties in selective cannulation of feeding vessels of the aneurysm and may lack durability due to refilling of the aneurysm from collateral 32,33 …”
Section: Discussionmentioning
confidence: 99%
“…The option of intervention method relied on aneurysm anatomy, patient's general condition, and surgeon preferences. Recently, the advantage of endovascular management on low perioperative morbidity and mortality is widely accepted [5,7,10] . In general, endovascular interventions have…”
Section: Interventionmentioning
confidence: 99%
“…Endovascular repair becomes increasingly popular in the field of vascular surgery because it is safe, effective, and less invasive. Chin et al's population-based evaluation in the management of visceral aneurysm demonstrated that endovascular management compared with open repair is associated with decreased mortality and complications and shorter hospital days [10] . They further recommended this method as the first alternative option.…”
Section: Accepted Manuscriptmentioning
confidence: 99%